Indonesian Higher Education's Entrepreneurial Curriculum: A Literature Review - Elpisah, Elpisah; Suarlin, Suarlin; Latang, Latang; Pada, Amir (Journal of Education Culture and Society, 2024)
Aim. This academic article conducts a careful systematic review of the entrepreneurship curriculum in Indonesian higher education, examining important aspects to uncover existing conditions and identify opportunities for improvement. Emphasising the urgent need for in-depth exploration of the implementation of entrepreneurship education.Methods. A systematic literature review serves as a basis for summarising publications in a particular field of study. Systematic literature review using the method, which consists of five different stages. These stages include defining eligibility criteria, describing sources of information, literature selection, data collection, and selection of data items. This method proves advantageous as it can serve as a starting point or proposal for further research and analysis.Results. Among the 31 papers carefully selected for analysis, two prominent themes emerged: the implementation of entrepreneurship education programs and the development of entrepreneurial learning within Indonesian entrepreneurial universities. Most of the extensively selected articles focus on these themes. This research examines student entrepreneurial competence, mentoring, and various forms of entrepreneurial learning within the framework of higher education in Indonesia.Conclusion. In reviewing the landscape of Indonesia’s higher education entrepreneurship curriculum, it becomes clear that while strides have been made, significant challenges remain. The uniqueness of Indonesia’s demographics, coupled with economic dynamics, underscores the urgency of fostering entrepreneurship education. Despite growing demand, research reveals deficiencies in the effectiveness of current programs, emphasising the need for comprehensive research. The dearth of English-language scientific literature and publications requires innovative approaches, such as categorising accessible digital resources, to gather insights into common practice.